Influence of prior 810-nm-diode intracanal laser irradiation on hydrophilic resin-based sealer obturation - Cacio Moura-Netto; Renato Miotto Palo; Samira Esteves Afonso Camargo; Carol Jent; Renato de Toledo Leonardo; Marcia Martins Marques (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Dentin wall structural changes caused by 810-nm-diode laser irradiation can influence the sealing ability of endodontic sealers. The objective of this study was to evaluate the apical leakage of AH Plus and RealSeal resin-based sealers with and without prior diode laser irradiation. Fifty-two single-rooted mandibular premolars were prepared and divided into 4 groups, according to the endodontic sealer used and the use or non-use of laser irradiation. The protocol for laser irradiation was 2.5W, continuous wave in scanning mode, with 4 exposures per tooth. After sample preparation, apical leakage of 50% ammoniacal silver nitrate impregnation was analyzed. When the teeth were not exposed to irradiation, the RealSeal sealer achieved the highest scores, showing the least leakage, with significant differences at the 5% level (Kruskal-Wallis test, p = 0.0004), compared with AH Plus. When the teeth were exposed to the 810-nm-diode laser irradiation, the sealing ability of AH Plus sealer was improved (p = 0282). In the RealSeal groups, the intracanal laser irradiation did not interfere with the leakage index, showing similar results in the GRS and GRSd groups (p = 0.1009).